Synthesis of vinylsilanes - Lim, D; Anderson, E (2012)
Vinylsilanes are versatile synthetic building blocks, which in recent years have played an increasing role in the synthesis of complex molecules. This article provides an overview of regio- and stereoselective methods for the preparation of vinylsilanes, focusing- on the most flexible and synthetically practical routes to each substitution pattern. 1 Introduction 2 Acyclic Vinylsilanes 2.1 trans-1,2-Disubstituted Vinylsilanes 2.2 cis-1,2-Disubstituted Vinylsilanes 2.3 1,1-Disubstituted Vinylsilanes 2.4 1,1,2-Trisubstituted Vinylsilanes 2.5 1,2,2-Trisubstituted and Tetrasubstituted Vinylsilanes 3 Cyclic Vinylsilanes 3.1 Exocyclic vinylsilanes 3.2 Endocyclic vinylsilanes 4 Conclusions. © Georg Thieme Verlag Stuttgart · New York.